Efficacy of Endoscopic Evaluation and Hemostatic Intervention for Post-hemorrhoidectomy Bleeding - Katsuhisa Ohashi; Katsuhide Ohashi; Akinori Sasaki; Kazuyoshi Ota; Kazutomo Kitagawa (Journal of the Anus, Rectum and Colon)
Achieving hemostasis during post-hemorrhoidectomy bleeding (PHB) is often challenging owing to poor visibility within the anal canal. We investigated the feasibility of using endoscopy for observation and maintaining hemostasis during PHB. Endoscopic evaluation was performed in patients with normal vital signs and no severe pain or excessive bleeding was observed during proctoscopy. Hemostatic clipping was performed if the bleeding site was clearly identified. In cases with profuse bleeding and endoscopic hemostasis deemed difficult, surgical hemostasis was performed. Of the 14 patients who developed PHB during the 3-year study period, endoscopic observation was performed in 6 cases. Arterial bleeding was confirmed in five of these cases; while, spontaneous hemostasis had already occurred in the remaining case. Hemostasis was achieved with endoscopic clipping in all cases. The mean procedure time was 14.7 minutes with no adverse events or re-bleeding. Endoscopic evaluation for PHB provides a detailed view of the bleeding site and facilitates hemostasis using clips.